Increasing Interest of Learning Science Through The Guide Inquiry Approach to Basic Class III Students - Wiwik Mala Derita; Farida F (Postgraduate School, Universitas Negeri Padang, 2019)
Abstract: Low science learning outcomes are less interested and active in learning. This study aims to increase interest in learning science in third grade students of SD N 14 tapan. classroom action research (PTK), data obtained during the research process are analyzed qualitatively and quantitatively. The approach used in this study is the Inquri Guide approach with the following steps: (1) Orientation, (2) Formulating a problem, (3) Formulating a hypothesis, (4) Gathering data to prove the hypothesis, (5) Formulating a conclusion. The research data was obtained using tests, observations, and field notes. The results of each cycle carried out in the study have seen an increase, where in the first cycle showed that the average percentage of student interest reached 54.44% with the category of interest while in the second cycle the average percentage of student interest reached 73.72% with the category very interest. The average student learning outcomes in the first cycle reached 64, and in the second cycle reached 75. The average learning outcomes in the second cycle had exceeded the KKM (Minimum Completion Criteria) set by SD N 14, which was 65.